The role of Fusobacterium nucleatum in colorectal cancer: from carcinogenesis to clinical management. Issue 3 (1st September 2019) - Sun, Chun‐Hui; Li, Bin‐Bin; Wang, Bo; Zhao, Jing; Zhang, Xiao‐Ying; Li, Ting‐Ting; Li, Wen‐Bing; Tang, Di; Qiu, Miao‐Juan; Wang, Xin‐Cheng; Zhu, Cheng‐Ming; Qian, Zhi‐Rong
Abstract: Colorectal cancer (CRC) is a common malignant tumor that affects people worldwide. Metagenomic analyses have shown an enrichment of Fusobacterium nucleatum ( F. nucleatum ) in colorectal carcinoma tissue; many studies have indicated that F. nucleatum is closely related to the colorectal carcinogenesis. In this review, we provide the latest information to reveal the related molecular mechanisms. The known virulence factors of F. nucleatum promote adhesion to intestinal epithelial cells via FadA and Fap2. Besides, Fap2 also binds to immune cells causing immunosuppression. Furthermore, F. nucleatum recruits tumor‐infiltrating immune cells, thus yielding a pro‐inflammatory microenvironment, which promotes colorectal neoplasia progression. F. nucleatum was also found to potentiate CRC development through toll‐like receptor 2 (TLR2)/toll‐like receptor 4 (TLR4) signaling and microRNA (miRNA)‐21 expression. In addition, F. nucleatum increases CRC recurrence along with chemoresistance by mediating a molecular network of miRNA‐18a*, miRNA‐4802, and autophagy components. Moreover, viable F. nucleatum was detected in mouse xenografts of human primary colorectal adenocarcinomas through successive passages. These findings indicated that an increased number of F. nucleatum in the tissues is a biomarker for the diagnosis and prognosis of CRC, and the underlying molecular mechanism can probably provide a potential intervention treatment strategy for patients with F. nucleatum ‐associated CRC.